Підвищення ефективності організаційно-управлінської реструктуризації підприємства шляхом збільшення залученості персоналу - Шкрабак, І. В.; Skrabak, I. V. (Гельветика, 2024)
У статті обґрунтовано негативний вплив опору змінам, які виступають інструментом організаційно-управлінської реструктуризації підприємства. Панівні методи подолання опору змінам відповідають постулату про перевагу заходів зі зменшення сил опору порівняно з підвищенням потужності рушійних сил організаційних змін. Обґрунтовано позитивний вплив на ефективність реструктуризації такого чинника, як готовність персоналу до змін, яка підкріплена його прихильністю до підприємства. Визначено, що інструментом підвищення ефективності реструктуризації може виступати лише залученість персоналу до змін, яка включає в себе задоволеність працею і лояльність як невід’ємні складові. Запропоновані напрями формування драйверів підвищення залученості персоналу, їх складові і системи менеджменту підприємства, які потребуватимуть організаційних змін. Обґрунтовано доцільність включення до складових зазначених напрямів прекомунікацій з майбутніми працівниками організації і посткомунікацій з працівниками, які звільнилися.

The negative impact of resistance to organisational changes on the efficiency of organisational and managerial restructuring of enterprise was substantiated in the article. This is due to the significant expenditure of resources to overcome resistance. It was found that the most common methods of ensuring the effectiveness and efficiency of restructuring were aimed at overcoming resistance to change. It was substantiated that increasing the readiness of staff for organisational change has a positive impact on the effectiveness of restructuring, if it was accompanied by staff commitment to the organisation. The levels of commitment to the organisation were analysed and it was proved that the involvement of staff in the life of the company can be an instrument for improving the efficiency of restructuring. At the same time, job satisfaction and employee loyalty to the organisation are components of staff engagement. The author proposes directions of formation of drivers of increasing staff engagement, which include: alignment of personal goals with the goals of the organisation, corporate culture, interaction and communication. As components of the first area, satisfaction with working conditions, professional and social recognition, professional and career growth were proposed. The transformation of corporate culture was proposed to be aimed at strengthening such values as labour productivity, leadership, and teamwork. These directions of formation of drivers for increasing staff engagement should be implemented on the basis of transformation of the enterprise's motivation system. It was substantiated that the components of interaction and communication, in addition to the developed feedback from the company's employees, should include those that ensure the possibility of forming staff engagement even before the recruit starts working in the company with subsequent onboarding, as well as maintaining communication with employees who have left but may be useful to the enterprise. This direction of forming the drivers of staff engagement should be implemented through appropriate changes in the enterprise's communication system.
Efficiency increasing of organisational and management restructuring of the enterprise by increasing staff engagement
Keywords: організаційно-управлінська реструктуризація; ефективність; опір змінам; готовність до змін; залученість персоналу; інструмент; organisational and managerial restructuring; efficiency; resistance to change; readiness for change; staff engagement; tool